Penerapan Metode Estafet Writing untuk Meningkatkan Kemampuan Menulis Cerpen pada Siswa Kelas XI SMAN 21 Surabaya Tahun Ajar 2024/2025: Indonesia - Lukman Hadi Wibowo; Kaswadi; Denny Sofiastuti (Singular: Journal of Pedagogical Language, Literature, and Cultural Studies, 2025)
The purpose of this study was to improve students' skills in learning to write short stories (cerpen) using the estafet writing method with spinner media for class XI students of SMAN 21 Surabaya in the 2024/2025 academic year. The type of research used was classroom action research (CAR). The CAR model used was the C. Kemmis & Mc Taggart spiral model, which was implemented in three cycles, namely pre cycle, cycle I, and cycle II. Data collection techniques were test techniques. The research instrument used questions and observation sheets. The data analysis technique used was comparative descriptive. The study was conducted from September to November 2024 with 36 students as research subjects. The study results showed increased skills in writing short stories in groups using the estafet writing method and individually through a post-test. The percentage of group completion increased at the pre cycle, cycle I, and cycle II stages, which were 16.7%, 66.7%, and 100%. Meanwhile, the percentage of individual completion increased in the pre-cycle stage, cycle I, and cycle II to 19.5%, 72.2%, and 94.4%. Thus, the relay writing method can improve the ability to write short stories in grade XI students.